A non-lethal method for the sampling of the gut microbiota in Betta splendens - Pun, Ka Ieng; Jinatham, Vasana; Saidu, Muhammad Bashir; Sapage, Manuel; Popluechai, Siam; Antunes, André; Saninjuk, Kritsakorn; Gonçalves, David (Frontiers in Veterinary Science, 2026)
The gut microbiota is known to modulate brain function and behavior but the underlying mechanisms are still poorly understood. In particular, research on the impact of gut microbiota in aggressive behavior is scarce. The Siamese fighting fish (Betta splendens) has been increasingly used for studies of aggression but methodologies for gut microbiota-aggression studies are lacking for the species. Here, we compared the gut microbial diversity in B. splendens using a conventional lethal gut sampling technique and a non-lethal mouth swabbing method. Bacterial communities were profiled by 16S rRNA gene sequencing targeting the V3–V4 region. Alpha diversity analyses, including observed amplicon sequence variants (ASV), Shannon diversity index, Chao1 richness estimator, and Faith’s phylogenetic diversity, revealed no statistically significant differences between sampling methods when compared using Kruskal–Wallis and Wilcoxon rank-sum tests. Beta diversity analyses using Bray–Curtis dissimilarity index through PERMANOVA also held comparative results, although phylogenetically informed metrics, such as weighted UniFrac and generalized UniFrac, revealed significant compositional divergence between the two sampling methods, with the swab collection method holding generally higher values. The swab method identified most of the microbial groups also identified by lethal gut sampling, plus some additional taxa that are potentially only present in the upper gut. Taken together, our findings support the use of non-lethal mouth swabbing as a viable and ethically preferred alternative to traditional sampling of the intestine for characterizing the gut microbiota of B. splendens. This technique, first applied in a small fish, may be particularly valuable in longitudinal studies to assess changes in gut microbiota in relation to aggression in B. splendens, enabling repeated sampling over time to investigate how microbial community dynamics correlate with the development, expression, or modulation of aggressive behavior.